Effects of acepromazine on the cardiovascular actions of dopamine in anesthetized dogs - Monteiro, Eduardo R.; Teixeira Neto, Francisco José [UNESP]; Castro, Vanessa B.; Campagnol, Daniela (Blackwell Publishing, 2007)
To evaluate the effects of acepromazine maleate on the cardiovascular changes induced by dopamine in isoflurane-anesthetized dogs.Prospective, randomized cross-over experimental design.Six healthy adult spayed female dogs weighing 16.4 +/- 3.5 kg (mean +/- SD).Each dog received two treatments, at least 1 week apart. Acepromazine (0.03 mg kg(-1), IV) was administered 15 minutes before anesthesia was induced with propofol (7 mg kg(-1), IV) and maintained with isoflurane (1.8% end-tidal). Acepromazine was not administered in the control treatment. Baseline cardiopulmonary parameters were measured 90 minutes after induction. Thereafter, dopamine was administered intravenously at 5, 10, and 15 mu g kg(-1) minute(-1), with each infusion rate lasting 30 minutes. Cardiopulmonary data were obtained at the end of each infusion rate.Dopamine induced dose-related increases in cardiac index (CI), stroke index, arterial blood pressure, mean pulmonary arterial pressure, oxygen delivery index (DO2I) and oxygen consumption index. In the control treatment, systemic vascular resistance index (SVRI) decreased during administration of 5 and 10 mu g kg(-1) minute(-1) of dopamine and returned to baseline with the highest dose (15 mu g kg (-1) minute(-1)). After acepromazine treatment, SVRI decreased from baseline during dopamine administration, regardless of the infusion rate, and this resulted in a smaller increase in blood pressure at 15 mu g kg (-1) minute(-1). During dopamine infusion hemoglobin concentrations were lower following acepromazine and this contributed to significantly lower arterial O-2 content.Acepromazine prevented the return in SVRI to baseline and reduced the magnitude of the increase in arterial pressure induced by higher doses of dopamine. However, reduced SRVI associated with lower doses of dopamine and the ability of dopamine to increase CI and DO2I were not modified by acepromazine premedication.Previous acepromazine administration reduces the efficacy of dopamine as a vasopressor agent in isoflurane anesthetized dogs. Other beneficial effects of dopamine such as increased CO are not modified by acepromazine.
Keywords: acepromazine; dog; dopamine; sympathomimetics